Strategi Manajemen Konflik untuk Meningkatkan Kolaborasi dan Kinerja dalam Konteks Pendidikan dan Organisasi - Dayuk Feqomara Dewi; Nayyifatul Fitriah; Kurnia Sari; Zenol Rosul; Mu’alimin Mu’alimin (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2025)
Conflict management strategies are key to creating harmonious collaboration and improving organizational performance in both educational and general organizational contexts. Poorly managed conflicts can hinder productivity and create tension, but with the right strategies, conflicts can be transformed into opportunities for innovation and process improvement. This study uses a literature review method to analyze various conflict management strategies, such as open communication, mediation, and routine evaluation, which are effective in resolving conflicts and fostering synergy among organizational members. The findings show that implementing these strategies can enhance cooperation, improve interpersonal relationships, and support the achievement of organizational goals optimally.